2014
DOI: 10.1155/2014/154106
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Constituents as Anticancer Agents: A Mechanistic View

Abstract: Exploring natural plant products as an option to find new chemical entities as anticancer agents is one of the fastest growing areas of research. Recently, in the last decade, essential oils (EOs) have been under study for their use in cancer therapy and the present review is an attempt to collect and document the available studies indicating EOs and their constituents as anticancer agents. This review enlists nearly 130 studies of EOs from various plant species and their constituents that have been studied so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
160
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(181 citation statements)
references
References 166 publications
5
160
0
6
Order By: Relevance
“…In other studies, it was demonstrated that some transcription factors were up-regulated by Frankincense extract. This resin also activated caspase dependent apoptotic pathway, Akt and Erk1/2, and suppressed the expression of CyclinD1 in some cancer cell lines (7,25). An important feature of necrosis was shown to elicit a proinflammatory response that might recruit immune cells to the tumor site, thereby increasing the efficacy of the chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 96%
“…In other studies, it was demonstrated that some transcription factors were up-regulated by Frankincense extract. This resin also activated caspase dependent apoptotic pathway, Akt and Erk1/2, and suppressed the expression of CyclinD1 in some cancer cell lines (7,25). An important feature of necrosis was shown to elicit a proinflammatory response that might recruit immune cells to the tumor site, thereby increasing the efficacy of the chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 In recent years, a large number of secondary metabolites, including essential oils (EOs) are considered as valuable sources for ingredients in food and pharmaceutical industries, cosmetics and medicinal applications for prevention and/or treatment of many diseases including neurodegenerative diseases, rheumatoid arthritis, diabetes, respiratory diseases, cardiovascular diseases, cancers and inflammatory and oxidative diseases. 2,3 EOs extracted from MAPs, contain 300 compounds such as limonene, -pinene, -myrcene, -elemene, caryophyllene, humulene, -farnesene, cembrene, kaurene, eucalyptol, camphorene, camphor, carveol, limonene oxide, caryophyllene oxide, farnesol, humulene epoxide, -bisabolene oxide, carvacrol, catechol, eugenol, isopropyl alcohol, butyl alcohol, perillyl alcohol, geraniol, nerol, safrole, sesquiterpenes, rosmarinic acid, nerolidol, benzophenone, bornyl acetate, ethyl acetate, vernolide, cinnamaldehyde, acetophenone, helenin, fumarin, benzofuran etc., that exhibit many biological properties including antibacterial, antifungal, antioxidant, antiulcer, antispasmodic, antiproliferative, antitumor, antihepatotoxic, and others. EOs have thus become a focal point to improve and maintain human health needs and treatment of the diseases with less side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils are complex mixtures of monoterpenes, sesquiterpenes and phenolics (Carson and Riley, 1995;Radulescu et al, 2004), and are known to have biological activity against cancer cell lines (Edris, 2007;Bhalla et al, 2013;Gautam et al, 2014;Raut and Karauppayil, 2014). Oil activity has been shown to be a sum of the effects of individual components based on the ratio of the different constituents and not necessarily on the quantity of one component (Kalemba and Kunicka, 2003;Houghton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%